Presuppositions in Dian Purnomo’s Novel “Perempuan yang Menangis kepada Bulan Hitam”: A Pragmatic Analysis - Rumilah, Siti; Langit, Aida Byru; Kusumaningtyas S., Bramuda Pramesti (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study aims to examine the presuppositions found in Dian Purnomo’s novel Perempuan yang Menangis kepada Bulan Hitam. This study used a qualitative descriptive method with data collection techniques using reading, observing, and note-taking techniques. The research object used is a novel by Dian Purnomo. The results found are lexical presuppositions, existential presuppositions, structural presuppositions, factive presuppositions, and counterfactual presuppositions in the novel. The phenomenon of presupposition in the novel Perempuan yang Menangis kepada Bulan Hitam is mostly found in the form of dialogue. The dialogue in the novel raises presuppositions. The presupposition results obtained based on dialogue have a communicative nature between speakers and hearers. The most presupposition data found in the novel is the type of lexical presupposition.